1978
DOI: 10.1542/peds.61.1.46
|View full text |Cite
|
Sign up to set email alerts
|

The Value of Pulsus Paradoxus in Assessing the Child With Status Asthmaticus

Abstract: The presence of pulsus paradoxus (PP) in 13 episodes of status asthmaticus in 12 children, ages 13 months to 15 years, was compared sequentially to a clinical score, peak expiratory flow rate (PEFR), heart rate, arterialized capillary pH, carbon dioxide pressure (Pco2), and the ratio of inspired oxygen to oxygen pressure (FIo2)/Po2) during the first 48 hours following admission. There was a significant correlation (P < .01) between the presence of a PP (≥ 5 mm Hg) and the clinical score (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1990
1990
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 42 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Measurement of PP during acute asthma exacerbations is currently recommended by national and international guidelines 11,17 and is one of the few objective bedside measures for assessment of asthma severity and the response to treatment. 4,8,18 However, manual determination of PP has been noted to be time-consuming to perform, 19 has variable interphysician consistency, 20 is difficult to obtain in a tachypneic child, 4 and is rarely used in clinical practice. 18,21 Furthermore, the ability of physicians to consistently and effectively measure blood pressure correctly has been reported to be poor.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Measurement of PP during acute asthma exacerbations is currently recommended by national and international guidelines 11,17 and is one of the few objective bedside measures for assessment of asthma severity and the response to treatment. 4,8,18 However, manual determination of PP has been noted to be time-consuming to perform, 19 has variable interphysician consistency, 20 is difficult to obtain in a tachypneic child, 4 and is rarely used in clinical practice. 18,21 Furthermore, the ability of physicians to consistently and effectively measure blood pressure correctly has been reported to be poor.…”
Section: Discussionmentioning
confidence: 99%
“…2 Although there is no consensus regarding the underlying pathophysiologic mechanisms of PP, 2,5 biventricular interdependence likely has an important role in both pericardial tamponade and acute asthma. 3 Prior studies evaluating the use of PP in children with asthma have found that PP of 15 mm Hg or greater predicts the need for hospitalization 6 and is associated with increased carbon dioxide pressure levels, [7][8][9] a decreased peak expiratory flow rate, 8 and decreased oxygen saturation (SpO 2 ). 10 National asthma guidelines for adults and children correlate PP with the severity of asthma: "absence of PP" (<10 mm Hg) in mild asthma; "may be present" (10-25 mm Hg) in moderate asthma; and "often present" (>25 mm Hg in adults and 20-40 mm Hg in children) in severe asthma.…”
mentioning
confidence: 99%